MENYELAMATKAN HARMONI KELUARGA: Implementasi Pusat Pembelajaran Keluarga di Klampis Ngasem Kota Surabaya - Diana Safitrii; Katerina Bataha (Halu Oleo University, 2024)
Domestic violence is a complex phenomenon that causes violence to harm family members. Domestic violence refers to behaviour involving physical, psychological, and sexual abuse by one family member against another. It often occurs in the context of a close relationship, such as between a married couple or between a parent and child. PUSPAGA Balai RW is a program created by the Surabaya Government that aims to provide prevention and handling services in overcoming family problems and providing protection to women and children in Surabaya. This research uses qualitative research methods with a descriptive approach. The result of this research is the implementation of the PUSPAGA Program in efforts to prevent and handle domestic violence in Klampis Ngasem Surabaya. From the results of the study, it was found that PUSPAGA can implement the prevention and handling of domestic violence in Klampis Ngasem Surabaya in accordance with the directions. Even so in the resource variable, there are still several obstacles that are often faced, such as the lack of PUSPAGA facilitators at Balai RW.